2022
DOI: 10.1155/2022/8788365
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Efficacy and Safety Analysis of Levofloxacin for the Prevention of Infection after Traumatic Osteoarthrosis and Internal Fixation: Systematic Review and Meta-Analysis

Abstract: Objective. Levofloxacin has been widely used in clinical anti-infection treatment; however, its adverse reactions to levofloxacin were also obvious in patients. Herein we aimed to systematically evaluate the clinical efficacy and safety of systemic administration of levofloxacin in the prevention of postoperative infection after traumatic osteoarthrosis and internal fixation. Methods. PubMed, Cochrane Library, OVID, EBSCO, CNKI, VIP database, and Wanfang Database were searched from December 1993 to December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Nevertheless, the intricate interplay between these two pharmaceuticals and their combined influence on the process of wound healing, specifically within the distinct domain of chronic prostatitis, remains ambiguous and necessitates comprehensive inquiry. 13,14 This research paper investigates the potential impact of levofloxacin, a broad-spectrum antibiotic, and tamsulosin, an alpha-blocker predominantly prescribed for the relief of urinary symptoms related to an enlarged prostate, on the process of wound healing in the aforementioned patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the intricate interplay between these two pharmaceuticals and their combined influence on the process of wound healing, specifically within the distinct domain of chronic prostatitis, remains ambiguous and necessitates comprehensive inquiry. 13,14 This research paper investigates the potential impact of levofloxacin, a broad-spectrum antibiotic, and tamsulosin, an alpha-blocker predominantly prescribed for the relief of urinary symptoms related to an enlarged prostate, on the process of wound healing in the aforementioned patients.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the antibiotic characteristics of levofloxacin can significantly contribute to the prevention or treatment of wound infections, the critical determinant in initiation of wound healing process. Nevertheless, the intricate interplay between these two pharmaceuticals and their combined influence on the process of wound healing, specifically within the distinct domain of chronic prostatitis, remains ambiguous and necessitates comprehensive inquiry 13,14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobials are commonly used clinically to prevent and treat perioperative infections; however, the use of antimicrobials tends to increase the metabolic burden on liver function and has a limited preventive effect 9,10 . Some studies have found that appropriate operating room nursing is beneficial for reducing the incidence of surgical‐site infection 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobials are commonly used clinically to prevent and treat perioperative infections; however, the use of antimicrobials tends to increase the metabolic burden on liver function and has a limited preventive effect. 9 , 10 Some studies have found that appropriate operating room nursing is beneficial for reducing the incidence of surgical‐site infection. 11 Refined nursing interventions in the operating room are key to the success of surgery and include proactively communicating with patients during the nursing period, conducting comprehensive preoperative assessments of all patients, actively controlling underlying diseases and preparing the patient for the surgery, as well as good control of medical equipment and disinfection norms to ensure the sterility of the surgical area, thus reducing the occurrence of infection and improving the quality of care.…”
Section: Introductionmentioning
confidence: 99%